"That's where the dollars are": understanding why community sports volunteers engage with intellectual disability as a form of diversity. Issue 3 (4th May 2021) - Storr, Ryan; Jeanes, Ruth; Spaaij, Ramón; Farquharson, Karen
ABSTRACT: Research question: This paper aims to provide new insights into why community sports volunteers engage with intellectual disability as a form of diversity, and how these drivers impact on the opportunities and activities provided for athletes with intellectual disabilities. Research methods: The authors use a critical diversity management framework, combined with theoretical tenets of ableism, to explore volunteers' engagement with disability. The paper draws on a ten-month ethnographic study undertaken in a community sports club in Melbourne, Australia, that had recently introduced two specialist teams for individuals with intellectual disabilities. Results and findings: The findings indicate the business case for diversity as a driver for the club to engage with sport for people with intellectual disabilities; this, in turn, created tension and conflict amongst volunteers, resulting in a separation of the disability team from the main club activity. Implications: Ableist discourses underpinned the business case for diversity held by some club volunteers, resulting in the disability team not being integrated into the club as part of its core business. Policy makers and advocates of diversity must critically consider the drivers of clubs for engaging in the different areas of diversity, and how this might impact on provision.